Assessing microplastic pollution in marine mammals: evidence from three cetacean species in the southeastern Black Sea - Onay, Hatice; Er, Akif; Minaz, Mert; Emanet, Muhammet; Ceylan, Yusuf; Akdemir, Tolga; Karslı, Barış; Dalgıç, Göktuğ (Frontiers in Marine Science, 2025)
Microplastic (MP) pollution has emerged as a pervasive environmental threat, with growing evidence of its accumulation across various marine trophic levels, including top predators such as cetaceans. This study investigates MP abundance, size distribution, morphology, color, and polymer composition in the gastrointestinal tracts (GITs) of three cetacean species sampled from the southeastern Black Sea. A total of seven individuals were examined, with MP abundances ranging from 5 to 139 particles per individual. Fiber-type MPs were predominant (75%), with black, green, and transparent colors being the most frequently observed. The majority of MPs were small in size, with an average length of 2002 ± 1961 µm, suggesting possible trophic transfer from lower-level organisms such as copepods and fish. Polymer analysis revealed polyamide (PA), polyacrylonitrile (PAN), and ethylene-vinyl acetate (EVA) as the most common polymer types, indicating both fishing gear and domestic wastewater as primary MP sources. Spatial patterns in stomach fullness and MP load suggest that local environmental conditions, such as fishing activity and tourism, influence exposure levels. The study highlights the significance of both incidental ingestion during feeding—especially through net interactions—and trophic transfer as key MP exposure pathways in cetaceans. These findings demonstrate the potential ecological risks posed by MPs at higher trophic levels and emphasize the urgent need for biodegradable alternatives to synthetic fishing gear and improved wastewater management. Moreover, collaborative efforts among local authorities and NGOs are recommended to raise awareness and support adaptive environmental management in the region.